Inequalities of Education as Consequences of Grouping Arrangements in Language Classes of Disadvantaged Children - Furcsa, Laura (International Dialogues on Education Journal, 2014)
This paper describes the potential effects of grouping arrangements (in particular ability grouping) for language education in classes for disadvantaged children in Hungarian primary schools. The findings of the present paper are based on a larger study which aimed at identifying the major problems faced by disadvantaged foreign-language learners and their teachers. The paper aims to construct a detailed and comprehensive picture of the process of language learning perceived by both the children and their teachers. The main research tool was in-depth interviewing, combined with classroom observations. The research used purposive sampling and focused on rural primary schools attended by a considerable number of disadvantaged children situated in Hungary. The findings indicate that ability grouping for language instruction is a prevalent form of arrangement; however, it seems to have long-lasting negative effects on the achievement of the children in lower ability levels.